(untitled) (Praxis Educativa, 2015)
Supported by the evidence found in documents produced by undergraduate and graduate students, the text is focused on representative samples of language practices, autobiography writing, and metacognitive reflections linked with text production from students at the higher education level, analyzed through Carlino (2005), Brito (2010), Natale (2012), Bidiña and Zerillo (2013), Navarro (2013) and others. In general, as an advance conclusion, it can be said that students complain that the intense monotoring carried out by the teaching staff at the beginning of the lerarning process decreases as the course is in progress, but they also show signs of having difficulties in the framing of the enunciator, and their papers manifest scarce rhetorical and pragmatic abilities, in spite of the two decades elapsed since the functional communicative approach for language teaching was officially prescribed in Argentina. Furthermore, students object the lack of common criteria among the teachers regarding the use of academic text formats, and demand institutional agreements or between the faculty members concerning the criteria for the evaluation of papers.